2009
DOI: 10.1111/j.1439-0264.2008.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Galanin‐Containing Nerve Fibres in Rat Tibia

Abstract: Galanin exerts tonic inhibition of nociceptive input to the central nervous system. Recently, this peptide was demonstrated in several neuronal and non-neuronal structures in bones and joints. In this study, the time of appearance and topographic localization of galanin-containing nerve fibres in bone were studied in rats from gestational day 16 (GD16) to postnatal day 21 (PD21). The tibia was chosen as a model of developing long bone and indirect immunofluorescence combined with confocal laser scanning micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the present study, the L4/5 DRGs were examined based on the previous findings showed that sciatic DRG neurons were normally located in lumbar ganglia L3-L6, and nearly 98-99% of all sciatic DRG perikaryal resided in the L4 and L5 DRGs (Swett et al, 1991), where L4 DRG contains somas of the majority of neurons with receptive fields in the hind paw (da Silva Serra et al, 2016). However, the sensory neurons innervating the periosteum of the tibia are confined predominantly to L3 and L4 DRGs (Gajda et al, 2004), and the soma of sensory neurons innervating the rat tibia are located predominantly in the L3 DRG (Ivanusic, 2009). We acknowledge the limitation of our study that it was not investigated in which afferents (bone, muscle, cutaneous, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the L4/5 DRGs were examined based on the previous findings showed that sciatic DRG neurons were normally located in lumbar ganglia L3-L6, and nearly 98-99% of all sciatic DRG perikaryal resided in the L4 and L5 DRGs (Swett et al, 1991), where L4 DRG contains somas of the majority of neurons with receptive fields in the hind paw (da Silva Serra et al, 2016). However, the sensory neurons innervating the periosteum of the tibia are confined predominantly to L3 and L4 DRGs (Gajda et al, 2004), and the soma of sensory neurons innervating the rat tibia are located predominantly in the L3 DRG (Ivanusic, 2009). We acknowledge the limitation of our study that it was not investigated in which afferents (bone, muscle, cutaneous, etc.)…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the disappearance of GAP-43-immunoreactive fibers in later stages of the development may reflect nerve fiber maturation (PGP 9.5 remains). Only a very limited number of papers have been published so far in which the authors systematically followed the innervation in long bone during the fetal and postnatal periods using immunolabeling for neuropeptides and general neuronal markers [Gajda et al, 2000[Gajda et al, , 2005[Gajda et al, , 2009Sisask et al, 1995Sisask et al, , 1996Hara-Irie et al, 1996]. Only a single study [Sisask et al, 1996] has described the development of autonomic nerve fibers in bone.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, a rodent model of rib-fracture found that galanin expression was increased in callus tissues with staining detected in cells (osteoprogenitor cells, osteoblasts, and chondrocytes) and in tissue matrices (cartilaginous, osseous, and periosteal) during bone healing; whilst serum galanin concentrations were consistently found to be increased at 2 weeks following fracture ( 59 ). In line with these findings, galanin-containing nerve fibres were observed in bone of rats from gestational day 16 to postnatal day 21 at various levels, ranging from the epiphyseal perichondria to the diaphyseal periosteum at gestational day 16; the bone marrow cavity as well as the inter-condylar eminence of the knee joint at postnatal day 1; the cartilage canals of both epiphyses at postnatal day 7; the secondary ossification centres at postnatal day 10; the bone marrow of both epiphyses at postnatal day 14; suggesting their sensory origin in various regions during skeletal development ( 79 ). In a mouse calvarial injection model, galanin treatment was found to facilitate bone formation associated with injury via the inhibition of cytokine production, such as excess TNF-alpha and IL-1beta, after bone injury ( 80 ).…”
Section: The Role Of Galanin Galp and Alarin In The Neuroendocrine Axismentioning
confidence: 99%